BENZENE TOXIC OOGENESIS OF CRAB, SCYLLA SERRATA (FORSKAL) - SUBHAS, M.; CHAKRAWARTHY, R.K.; SAROJINI, R.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
In the present probe the effect of lethal and sublethal concentration of petroleum hydrocarbon (Benzene) on ovar maturation of marine edible crab, Scyllaserrata (Forskal) was carried out. Lethal concentration 2.413 ml/2 lit and 1. ml/2 lit for 48 and 96 hrs, respectively caused damage to ovarian layer, vacuolization, dearrangement of oocytes a pycnosis of nutritive cells. Whereas sublethal concentration 0.24 ml/2 lit for 10 and 30 days showed destruction of proliferation zone and degeneration of oocytes.